The Effects of FDI on the Moroccan Economy: An Empirical Estimate from a Structural Model - SFAR, Souad BANNOUR Ep; MTAR, Kais (Asian Journal of Economic Modelling, 2017)
The primary aim of the present article is to study whether foreign direct investment (FDI) exerts positive or negative effects on the Moroccan economy. Thus, through a structural model of simultaneous equations, the effects of FDI were examined in terms of economic growth, foreign trade, human capital and domestic investment in Morocco. The empirical results of this study show that FDI clearly demonstrates significant and positive effects on the first three variables whereas, it appears that there is no significant correlation with the domestic investment variable.